2009
DOI: 10.1007/s11270-009-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Palladio, an Index of Trace Element Alteration for the River Bacchiglione Based on Rhynchostegium riparioides Moss Bags

Abstract: The concentration of Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sb, Se, V and Zn was measured in the aquatic bryophyte Rhynchostegium riparioides after a 4-week transplantation at 83 stations in seven main watercourses and three smaller tributaries of the basin of the River Bacchiglione (NE Italy). The study, carried out in 9 months, aimed at establishing a database for statistical analyses to define a novel index of water quality, specifically calibrated for moss bags, and suitable for bio-monitoring purposes where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…This behaviour has often been observed in P. riparioides by Cesa et al (2010Cesa et al ( , 2013, and the most probable reason is that the concentration in moss before exposure was close to the equilibrium state for the corresponding water concentration in the experimental site, which was very low, compared to that of other trace elements, as Table 1 suggests. The only exception was iron in P. riparioides, whose concentration was high in the water (up to 451 μg/l), but it was also in the moss (around 9000 mg/kg).…”
Section: Exposure Timesupporting
confidence: 58%
See 1 more Smart Citation
“…This behaviour has often been observed in P. riparioides by Cesa et al (2010Cesa et al ( , 2013, and the most probable reason is that the concentration in moss before exposure was close to the equilibrium state for the corresponding water concentration in the experimental site, which was very low, compared to that of other trace elements, as Table 1 suggests. The only exception was iron in P. riparioides, whose concentration was high in the water (up to 451 μg/l), but it was also in the moss (around 9000 mg/kg).…”
Section: Exposure Timesupporting
confidence: 58%
“…Moss bags have been successfully used both for environmental monitoring and investigation, mostly in Europe (Bruns et al 1997;Carballeira et al 2001;Cenci 2000;Cesa et al 2006Cesa et al , 2010Figueira and Ribeiro 2005;Mersch and Reichard 1998;Rasmussen and Andersen 1999;Siebert et al 1996;Yurukova and Gecheva 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another interpretation is that these zones have a lower percentage of vegetation cover as a result of higher urbanization. For example, Cesa et al [27] show that the concentration of such metals (e.g., Ca, Co, and Mn) gradually increases with urbanization and lower degrees of vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Al, Cr, Pb, and V did not vary significantly among zones of the Zamora River, but lower concentrations were found in the control. Samecka et al [ 26 ], Cesa et al [ 27 ], and Herrera-Núñez et al [ 29 ] showed that the concentration of these metals in urban rivers is mainly due to the activities of textile and manufacturing industries, which are not present along the Zamora urban river. In addition, concentrations of these metals in natural waters are highly influenced by the presence of acid rain and atmospheric deposits [ 30 ], and stone extraction activities that affect deep beds [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomonitoring studies usually involve measurement of the total concentrations of individual contaminants in bryophyte tissues (Carballeira and López, 1997;Samecka-Cymermann and Kempers, 1998;Cesa et al, 2010). However, determination of the concentrations of contaminants accumulated in different cellular form.…”
Section: Introductionmentioning
confidence: 99%